2015
DOI: 10.1099/mic.0.000163
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of (R)-3-hydroxybutyrate is regulated by the enhancer-binding protein PA2005 and the alternative sigma factor RpoN in Pseudomonas aeruginosa PAO1

Abstract: The metabolism of (R)-3-hydroxybutyrate is regulated by the enhancer-binding protein PA2005 and the alternative sigma factor RpoN in Pseudomonas aeruginosa PAO1 Apart from the numerous studies that had focused on the biochemical characterization of BdhA, there was nothing known about the assimilation of (R)-3-HB in Pseudomonas, including the genetic regulation of bdhA expression. This study aimed to define the regulatory factors that govern or dictate the expression of the bdhA gene and (R)-3-HB assimilation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
(35 reference statements)
0
16
0
Order By: Relevance
“…In contrast, the acetate-minimal media used for these specific experiments were not supplemented with gentamicin due to the presence of sulfate in the purchased antibiotic preparation (gentamicin sulfate). Previous studies by our group have shown that the addition of an antibiotic for plasmid selection is not necessary for genetic complementation experiments involving P. aeruginosa (32,35).…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, the acetate-minimal media used for these specific experiments were not supplemented with gentamicin due to the presence of sulfate in the purchased antibiotic preparation (gentamicin sulfate). Previous studies by our group have shown that the addition of an antibiotic for plasmid selection is not necessary for genetic complementation experiments involving P. aeruginosa (32,35).…”
Section: Methodsmentioning
confidence: 93%
“…The msuE and sfnG PCR products were gel purified and subsequently cloned into pJET1.2 (Thermo Fisher Scientific), yielding the plasmids pZS458 and pKSF01, respectively. The Cy5-labeled msuE and sfnG probes were generated by PCR comprised of the Cy5-labeled primers JRH05.f and JRH05.r, which anneal specifically to pJET1.2 (35), and either pZS458 or pKSF01 as the template. The resulting Cy5-labeled msuE and sfnG PCR products were gel purified and quantified using a NanoDrop spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
“…It was originally identified as a sigma factor required for transcription of the genes involved in nitrogen assimilation (Hirschman, Wong, Sei, Keener, & Kustu, ; Reitzer & Schneider, ). However, a great deal of evidence has now accumulated that RpoN also controls many other biological activities in bacteria, ranging from utilization of alternative carbon sources (Lundgren, Harris, Serwar, Scheel, & Nomura, ) and biodegradation of pollutants (Shingler, ) to motility (Dasgupta et al., ; Saldias, Lamothe, Wu, & Valvano, ; Totten, Lara, & Lory, ), and biofilm formation (Saldias et al., ; Thompson, Webb, Rice, & Kjelleberg, ; Wolfe, Millikan, Campbell, & Visick, ). It has been shown that RpoN controls flagellum‐mediated motility in B. cenocepacia , which was found to be essential for biofilm formation in microtiter trays (Saldias et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…PCR was used to amplify the 5=-regulatory regions adjacent to the open reading frames (ORFs) for exaC, PA4022, and eat. The amplified 5=-regulatory regions (850 bp for exaC, 986 bp for PA4022, 2,716 bp for eat, and 928 bp for truncated eat) were then fused to the ␤-galactosidase (lacZ) ORF of E. coli through PCR (24,27). The PA4022::lacZ, eat:: lacZ, and truncated eat::lacZ fusions were subcloned into the XbaI site of ⌬Plac-pBBR1MCS-5 (24) to yield the plasmids pBRL601, pBRL678, and pBRL597, respectively.…”
Section: Methodsmentioning
confidence: 99%